Ethical issues of randomized controlled trials - Sarker, Jyotirmoy (Bangladesh Journal of Bioethics, 2014)
Clinical trials involve the application of different medical interventions on human participants. Randomized controlled trials involve different groups of human subjects undergoing different clinical interventions. This process ensures bias free subject allocation which leads to a way to statistically establish the research result. Strict ethical guidance is necessary from selection of participants to the analysis of trial results. Without proper guidance the trial participants would be subjected to unethical experiments. Before starting the randomized controlled trials the investigators must meet all ethics issues. The institutional review board (IRB) must check whether all ethical demands are met or not before permitting the research. DOI: http://dx.doi.org/10.3329/bioethics.v5i1.18441 Bangladesh Journal of Bioethics 2014 Vol.5(1): 1-4